Humour et création lexicale dans le discours révolutionnaire du Hirak algérien - Benazouz, Nadjiba; Refrafi, Soraya (Linguistik Online, 2022)
This contribution is intended to be a descriptive and analytical study of the vehicular lexical processes of humor in the revolutionary discourse of the Algerian Hirak. Our reflection revolves around the following problem: what are the most productive lexical creation processes for humor in the revolutionary discourse of Hirak in Algeria? Our study would be quantitative in the measure of making statistics on the number of lexes generated by each process and qualitative in the sense of resorting to the contextualization in order to find the source meaning of humor for each lexis. For the purposes of this present research, we have collected 54 lexes that appeared in the revolutionary speech on Facebook pages, from 22 February 2019 until 31 October 2020, a period of moments of popular protest, known as Algerian Hirak, in fact, we first try to classify the collared lexis according to the categories of humor, taking inspiration from the work of P. Charaudeau (2006), then we identify the different creative processes mobilized in each category, in us. Referring to the typology of Pruvost/Sablayrolles (2016).